Direct 2H NMR Observation of the Proton Mobility of the Acidic Sites of Anhydrous 12‐Tungstophosphoric Acid. Issue 9 (16th April 2013) - Kolokolov, Daniil I.; Kazantsev, Maxim S.; Luzgin, Mikhail V.; Jobic, Hervé; Stepanov, Alexander G.
<x xml:space="preserve">Abstract</x> Flip and hop before you′re caught! The proton dynamics of solid 12‐tungstophosphoric acid (TPA) is probed by solid‐state 2H NMR in a temperature range from 293–503 K. Protons of TPA are shown to be involved in two types of molecular motion (see picture): the anisotropic local two‐site flipping between the two possible orientations of the OH bond at bridged oxygens of the Keggin anion, and the isotropic diffusion by hopping between neighboring surface oxygens of the anion.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>